Rehabilitation of Athletes With Hamstring Strain Injury: SONAFE-Brazil Clinical Practice Guideline - Bruno Manfredini Baroni; Rodrigo Ribeiro de Oliveira; Albino Luciano Abreu Pereira; Felipe Coimbra Meira; Filipe Abdalla dos Reis; Flavio Fernandes Bryk; Luiz Hespanhol; Katherinne Ferro Moura Franco; Larissa Santos Pinto Pinheiro; Natalia Franco Neto Bittencourt; Aline Carla Araújo Carvalho; Daniel Ferreira Moreira Lobato; et al. (Journal of Orthopaedic & Sports Physical Therapy, 2026)
The National Society of Sports Physical Therapy (SONAFE-Brazil), the official organization representing sports physical therapists in Brazil, developed this Clinical Practice Guideline to support clinicians and athletes in managing hamstring strain injury. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was employed to address the clinical question: “Which interventions provided by physical therapists improve rehabilitation outcomes in athletes with hamstring strain injury?” The guideline provides an updated and targeted synthesis of evidence from randomized clinical trials, offering practical guidance to inform clinical decision-making by physical therapists across diverse health care and sports settings.